ANALISIS EFISIENSI USAHA INDUSTRI TENUN GEDOGAN DI DESA PRINGGASELA KECAMATAN PRINGGASELA KABUPATEN LOMBOK TIMUR - Tuti Alawiyah; Wahyu Hidayat Riyanto; Hendra Kusuma (Program Studi Ekonomi Pembangunan, 2019)
The purpose of this study was to analyze the business income of the gedogan weaving industry, analyze the level of business efficiency of the gedogan weaving industry, and analyze the marketing channels of the gedogan weaving industry, and analyze the marketing channels of the gedogan weaving industry in Pringgasela Village, Pringgasela District, East Lombok Regency. The method used in this research is descriptive with the unit of analysis, which is a craftsman who works on the gedogan weaving industry in Pringgasela Village. In this study using a sample of 45 respondents. The data obtained were analyzed using income analysis, R / C ratio analysis and descriptive analysis. The results of this study indicate that the average income received per month amounted to Rp936,543.17 with an R / C ratio of 1.88. The marketing channel taken by craftsmen through two channels, namely channel one, the craftsman directly sells the products to the final consumer and the channel of the two craftsmen through the retailer then to the final consumer. The obstacles faced by craftsmen are marketing difficulties (52.00%), capital (34.00%) and raw materials (14.00%)